Oxone®/KI-Mediated Nitration of Alkenes and Alkynes: Synthesis of Nitro- and β-Iodonitro-Substituted Alkenes - Sornsiri Hlekhlai (2018)
© Copyright 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Oxone® (2KHSO5·KHSO4·K2SO4) was used to promote the nitration of alkenes and alkynes with sodium nitrite (NaNO2) and potassium iodide (KI). This stable, easy-to-handle, and environmentally benign oxidant was used under mild conditions (room temperature) and provided short reaction times. Styrene derivatives that did not contain electron-donating groups afforded the corresponding nitro alkenes in moderate to good yields, whereas aliphatic alkenes and electron-deficient alkenes were not good substrates. Under similar reaction conditions, aryl alkynes yielded β-iodonitro alkenes. Oxone® (2KHSO5·KHSO4·K2SO4) was used to promote the reactions of alkenes and alkynes with sodium nitrite (NaNO2) and potassium iodide (KI) to afford the corresponding nitro and β-iodonitro-substituted alkenes, respectively, in moderate to good yields.